The Screening Research of Anti-Inflammatory Bioactive Markers from Different Flowering Phases of Flos Lonicerae Japonicae - Jiang, Min (Public Library of Science, 2014)

(untitled)
Flos Lonicerae Japonicae (FLJ) is an important cash crop in eastern Asia, and it is an anti-inflammatory Traditional Chinese Medicine. There are large variations in the quality of the marketed FLJ products. To find marker ingredients useful for quality control, a tandem technology integrating ultra-performance liquid chromatography/quadrupole time-of-flight mass spectrometry (UPLC-Q/TOF), principal component analysis (PCA), heat map analysis and hierarchical cluster analysis coupled with a NF-κB luciferase reporter gene assay were used to identify the different ingredients from the green bud, white bud, flowering stage and leaf stages, as well as to screen the anti-inflammatory activity of FLJ compositions. As flowering progressed, the anti-inflammatory effects of FLJ gradually decreased; however, chlorogenic acid, swertiamarin and sweroside should be used to evaluate the quality of FLJ products.